2010
DOI: 10.1007/s12035-010-8153-1
|View full text |Cite
|
Sign up to set email alerts
|

Huntington’s Disease and Group I Metabotropic Glutamate Receptors

Abstract: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder characterized by involuntary body movement, cognitive impairment and psychiatric disturbance. A polyglutamine expansion in the amino-terminal region of the huntingtin (htt) protein is the genetic cause of HD. Htt protein interacts with a wide variety of proteins, and htt mutation causes cell signaling alterations in various neurotransmitter systems, including dopaminergic, glutamatergic, and cannabinoid systems, as well as trophic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 145 publications
(125 reference statements)
0
23
0
Order By: Relevance
“…These findings suggest that alterations in CBR1 or other components of the signaling pathways of striatal LTD could contribute to the corticostriatal plasticity defects in HD. Accordingly, patients with HD and mouse models display alterations in molecular components of striatal LTD, including cannabinoid receptors (38)(39)(40) and the mGluR5 signaling pathway (41)(42)(43). Previous studies have shown that using an agonist for CBR1 (WIN 55,212-2) (44) or mGluR5 (42,45) modulators in HD mouse models ameliorates several alterations associated with corticostriatal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that alterations in CBR1 or other components of the signaling pathways of striatal LTD could contribute to the corticostriatal plasticity defects in HD. Accordingly, patients with HD and mouse models display alterations in molecular components of striatal LTD, including cannabinoid receptors (38)(39)(40) and the mGluR5 signaling pathway (41)(42)(43). Previous studies have shown that using an agonist for CBR1 (WIN 55,212-2) (44) or mGluR5 (42,45) modulators in HD mouse models ameliorates several alterations associated with corticostriatal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we sought to investigate a link between the effects of MA on mGluR5 and NF-κB activation. Since the classical Huntington's disease pathway involves activation of the Akt/PI3K pathway, which is mediated via the mGluR5 receptor [54], we hypothesized a role for Akt/PI3K in the signaling cascade induced by MA. Our results support this hypothesis, because the antagonist for Akt/PI3K abrogated MA-mediated expression of IL-6 and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, specific roles for mGluRs have been suggested, such as abnormal LTD production in fragile X syndrome (Bear and others 2004; Goebel-Goody and Lombroso 2012; Zhang and Alger 2010), and group I mGluR involvement in endocannabinoid control of synaptic processing in schizophrenia and addiction (Melis and others 2004), but for the most part, the actual role of mGluRs in various diseases remains to be elucidated or even suggested. Cognitive diseases that have been so far implicated with regard to mGluR functioning include schizophrenia, anxiety disorders, mental retardation, fragile X syndrome and autism, Alzheimer's, Parkinson's, Huntingdon's, anxiety, depression, addiction, and epilepsy (Alexander and Godwin 2006a; Harrison and others 2008; Huang and others 2007; Luscher and Huber 2010; Marek 2010; Ribeiro and others 2011; Tamminga 2006; Ure and others 2006; Wong and others 1999). …”
Section: Cortical and Thalamic Mglurs And Diseasementioning
confidence: 99%